Pengaruh Sales Growth, Leverage, dan Aktivitas Perusahaan Terhadap Tingkat Financial Distress Pada Perusahaan Tekstil & Garmen Periode 2018-2023 - Kayla Andira; Raden Nasution (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Indonesia’s textile and garment industry is under considerable pressure due to trade imbalances, increasing illegal imports, and low operational efficiency, which have collectively triggered a wave of corporate bankruptcies. This study aims to analyze the effect of Sales Growth, Leverage (Debt to Equity Ratio), Inventory Turnover (ITO), and Total Asset Turnover (TATO) on Financial Distress among textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. A quantitative method was employed using descriptive and verificative statistical approaches. The research population consisted of 17 companies, from which 11 companies were selected as samples through purposive sampling, resulting in 66 firm-year observations. Data analysis was conducted using binary logistic regression with the assistance of IBM SPSS Statistics 27. The simultaneous test results indicate that all four independent variables significantly influence Financial Distress. Partially, Leverage has a significant positive effect, Total Asset Turnover has a significant negative effect, while Sales Growth and Inventory Turnover show no significant impact. The coefficient of determination shows that the model explains 67.3% of the variance in Financial Distress, with the remaining 32.7% attributed to other variables not included in the model. These findings highlight the critical role of capital structure and asset utilization efficiency in mitigating financial distress risk, rather than relying solely on sales growth or inventory turnover.